Exploring the Impact of ML NET (http://ml.net/) on Healthcare Predictive Analytics and Patient Care - Rajashree Manjulalayam Rajendran (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2022)
Machine Learning (ML) has emerged as a transformative force in various industries, and its application in healthcare holds great promise for improving patient outcomes and operational efficiency. This paper delves into the impact of ML.NET, a cross-platform, open-source machine learning framework, in the healthcare domain. Specifically, the focus is on predictive analytics and its role in advancing patient care. The integration of ML.NET into healthcare systems has facilitated the development of predictive models that harness the power of machine learning algorithms. These models analyze vast datasets, including patient records, medical images, and clinical notes, to identify patterns and make predictions. By leveraging ML.NET's capabilities, healthcare providers can enhance their decision-making processes, enabling more accurate and timely diagnoses. Despite the potential benefits, the paper also discusses challenges and considerations associated with implementing ML.NET in healthcare. This paper presents a comprehensive exploration of the impact of ML.NET in healthcare, with a specific emphasis on predictive analytics and its transformative effects on patient care. By harnessing the capabilities of ML.NET, healthcare organizations can usher in a new era of data-driven decision-making, ultimately leading to improved patient outcomes and a more efficient healthcare ecosystem.